The Effectiveness of the Combination of Spiritual Emotional Freedom Technique and Slow Deep Breathing in Lowering Blood Pressure Reduction in Hypertensive Patients at UPT Puskesmas Pasundan, Bandung City - Nyayu Nina Putri Calisanie; Ira Santika (STIKep PPNI Jawa Barat, 2022)
Aims: Hypertension is the leading cause of death from stroke worldwide and a factor that exacerbates myocardial infarction if not treated properly. Hypertension in addition to causing physical injury can also cause emotional wounds such as stress. The combination of spiritual emotional freedom techniques and slow deep breathing can lower blood pressure in folks with high blood pressure as a result of because it may be a non-pharmacological treatment which will heal emotional wounds equivalent to stress. Purpose: To decide the effectiveness of a aggregate of spiritual emotional freedom techniques and slow deep breathing decreasing blood stress in hypertensive patients. Methods: This study used a quasi-experimental control group design with a pretest-posttest and a random test. The sample was selected by means of a targeted sampling of uo to 58 respondents, namely 29 intervention groups and 29 control groups. The instruments used are a digital sphygmomanometer, a chart and a notebook. Results: There became a lower in systolic blood strain with the aid of using 24.20 mmHg and diastolic with the aid of using 7.55 mmHg. The effect of the ANCOVA test, the p-value of systolic 0.000 (p<0.05) and diastolic 0.002 (p<0.05) which suggests a significant conclusion. Conclusion: The combination therapy of spiritual emotional freedom and slow deep breathing is powerful in decreasing systolic and diastolic blood strain in hypertensive patients.